2017
DOI: 10.1021/acs.biochem.7b00894
|View full text |Cite
|
Sign up to set email alerts
|

The G126V Mutation in the Mouse Prion Protein Hinders Nucleation-Dependent Fibril Formation by Slowing Initial Fibril Growth and by Increasing the Critical Concentration

Abstract: The middle disordered hydrophobic region of the prion protein plays a critical role in conformational conversion of the protein, with pathogenic as well as protective mutations being localized to this region. In particular, it has been shown that the G127V mutation in this region of the human prion protein (huPrP) is protective against the spread of prion disease, but the mechanism of protection remains unknown. In this study, quantitative analyses of the kinetics of fibril formation by wild-type mouse prion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 72 publications
3
16
1
Order By: Relevance
“…The measured lag phase was 47 ± 2 h for the mixing sample. These kinetic analyses are similar to the quantitative comparison of moPrP(G126V) and WT moPrP 72 . These unique dynamic structural features might be responsible for the prion disease-resistance effect of the G127V mutant 20,21 .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The measured lag phase was 47 ± 2 h for the mixing sample. These kinetic analyses are similar to the quantitative comparison of moPrP(G126V) and WT moPrP 72 . These unique dynamic structural features might be responsible for the prion disease-resistance effect of the G127V mutant 20,21 .…”
Section: Discussionsupporting
confidence: 66%
“…In the G127V mutant, the surface electrostatic potential distribution on the region encompassing the α1 and α3 helices is diametrically distinct from those in the WT and the f CJD-associated E200K mutant 26 . The alterations of HuPrP(G127V) in both the geometric packing and electrostatic potential distribution combined with the close atomic distances between SS2 and the disulfide bridge, might prohibit rearrangement of the disulfide bridge, aggregation and fibrillization as previously published results 16,33,54,72 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, we found no direct microscopic evidence suggesting that new nuclei are produced on the surfaces of amyloid fibrils, raising the question of whether the secondary nucleation is operative in amyloid formation by PrP. A recent study also demonstrated that the classic nucleation-polymerization model is sufficient to reproduce the early-time behavior of amyloid formation by WT PrP (51). Therefore, we currently believe the classic nucleation-polymerization model, which includes only primary nucleation and elongation as the dominant reactions, and attribute the different t lag values shown in Fig.…”
Section: Caveats Of the F-value Analysiscontrasting
confidence: 68%
“…S6 A and B). Rather, des117 aggregation displayed flat concentration dependence, similar to other folded proteins, such as prion protein and light chain amyloid formation (27)(28)(29). This could reflect a strong influence of conformational transition on the kinetics or the presence of alternative aggregation pathways.…”
Section: Anti-amyloid Compound Egcg Slows the Aggregation Of Desminmentioning
confidence: 84%